MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN KEGIATAN BELAJAR MENGAJAR DI SD IT KANZUS DARUL FALAH TERBANGGI BESAR LAMPUNG - Siti Nurjanah; Endang Ekowati; Firmansyah (UNISAN JURNAL, 2025)
This study aims to describe the management of educational facilities and infrastructure to improve teaching and learning activities at SD IT Kanzus Darul Falah Terbanggi Besar, Lampung. The background of this study is the importance of the availability and management of adequate infrastructure as a key element in creating an effective, conducive, and high-quality learning process. Good facilities, such as learning media, books, technology devices, and classroom facilities, significantly influence student learning motivation. Similarly, infrastructure such as classrooms, libraries, prayer rooms, and the school environment plays a significant role in supporting a comfortable and productive teaching and learning process. This study used a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation. The results indicate that the management of facilities and infrastructure at SD IT Kanzus Darul Falah is carried out through four main stages: planning, procurement, maintenance, and evaluation. During the planning stage, the school conducts a needs analysis based on the number of students, the development curriculum, and the condition of existing facilities. Procurement is carried out in stages through BOS funds, the school committee, and the school administration. and support from the foundation's management institution. Maintenance is carried out through routine cleaning activities, periodic facility checks, and repairs when damage is discovered. Meanwhile, evaluations are conducted to assess the suitability of facilities for learning needs and the effectiveness of their use by teachers and students. Overall, effective facility and infrastructure management at SD IT Kanzus Darul Falah has been proven to have an impact on improving the quality of teaching and learning activities. A clean environment, well-organized classrooms, and adequate learning facilities create a comfortable learning atmosphere, increase student motivation, and support teachers in optimally delivering material.